Are Welsh primary schools Sunproofed? Results of a national survey, part 1: scoping the landscape of sun safety policies in Wales - Julie Peconi (Clinical and Experimental Dermatology, 2024)
BackgroundSchools with formal sun safety polices generally show better sun safety practices than schools without.ObjectivesTo understand the extent to which Welsh primary schools have sun safety policies; to identify the key characteristics of policies; to assess whether policy adoption varies by school characteristics; and to consider what support schools need to develop sun safety policies.MethodsAn online multiple-choice survey on sun safety was distributed to all 1241 primary schools in Wales.ResultsIn total, 471 (38.0%) schools responded. Of these, 183 (39.0%) reported having a formal sun safety policy. Welsh medium schools (P = 0.036) and schools in North Wales (P = 0.008) were more likely to report having a policy. Schools with a higher percentage of pupils receiving free school meals (P = 0.046) and with lower attendance rates (P = 0.008) were less likely to report having a sun safety policy. The primary reasons for schools not having a policy included being ‘not aware of the need’ (34.6%); ‘need assistance with policy or procedure development’ (30.3%); and ‘not got around to it just yet’ (26.8%).ConclusionsWith less than half of schools reporting a sun safety policy and variation in the presence/absence of a policy by school characteristics, our survey revealed inconsistency in formal sun safety provision in Welsh schools. The findings also suggest that schools are unaware of the importance of sun safety and need support to develop and implement policies. This snapshot of the current situation in primary schools in Wales provides a basis upon which the comprehensiveness, effectiveness and implementation of sun safety policies can be further evaluated.